Lipidomics revealed alterations in glycerophospholipid metabolism in skin squamous cell carcinoma - Mei, Li-Hong; Gan, Hui-Hui; Wang, Hong-Feng; Xu, Guoxiong; Ye, Xuan-Guang; Yang, Gao (Frontiers in Molecular Biosciences, 2024)
Background: Skin squamous cell carcinoma (SCC) is a prevalent malignancy, and dysregulated lipid metabolism has been implicated in its pathogenesis. However, detailed characterization of lipid alterations in SCC remains limited.We analyzed lipid metabolic variations in tissue samples from 34 SCC patients and adjacent healthy tissues (located more than 1 cm from the tumor margin) using liquid chromatography-mass spectrometry (LC-MS). Data visualization and discriminatory lipid profiles were identified using principal component analysis (PCA) and sparse partial least squares discriminant analysis (sPLS-DA). Key lipids involved in the SCC metabolism were identified and further validated using an external data set (from a previous study, which similarly explored lipid profiles in oral SCC using lipidomics approaches). Pathway enrichment analysis was conducted to elucidate the metabolic pathways associated with these key lipids.Results: Eight lipids were identified by comparing SCC and healthy tissues including PI(16:0/22:4),